Optically-excited excitonic states in semiconductor superlattices - Lachaine, Jean-Marc (My University, 2002)
An efficient method for calculation of the exciton states in type-I superlattices is developed and demonstrated. The model, based on the work of Dignam & Sipe [Phys. Rev. B 43,4097 (1991)], includes bound and quasi-continuous two-well exciton eigenstates as a basis in which to expand the superlattice exciton eigenstates. This basis is used to calculate the excitonic absorption spectra for two different type-I superlattices as a function of the applied static field. The results are found to be in very good agreement with the experimental results of Holfeld et. al [Phys. Rev. Lett. 81, 874 (1998)] for the 67A/17A superlattice and with those of Agullo-Rueda et. al [Phys. Rev. B 41, 1676 (1990)] for the 40A/40 A superlattice. On the basis of these results, this method should be ideal for use in the calculation of nonlinear and coherent effects in optically excited semiconductor superlattices.
Keywords: Exciton theory; Superlattices as materials (Optical properties)